Experimental Flat-Panel High-Spatial-Resolution Volume CT of the Temporal Bone - Gupta, Rajiv (AJNR Am J Neuroradiol, 2004)
BACKGROUND AND PURPOSE: A CT scanner employing a digital flat-panel detector is capable of very high spatial resolution as compared with a multi-section CT (MSCT) scanner. Our purpose was to determine how well a prototypical volume CT (VCT) scanner with a flat-panel detector system defines fine structures in temporal bone. METHODS: Four partially manipulated temporal-bone specimens were imaged by use of a prototypical cone-beam VCT scanner with a flat-panel detector system at an isometric resolution of 150 μm at the isocenter. These specimens were also depicted by state-of-the-art multisection CT (MSCT). Forty-two structures imaged by both scanners were qualitatively assessed and rated, and scores assigned to VCT findings were compared with those of MSCT. RESULTS: Qualitative assessment of anatomic structures, lesions, cochlear implants, and middle-ear hearing aids indicated that image quality was significantly better with VCT (P < .001). Structures near the spatial-resolution limit of MSCT (e.g., bony covering of the tympanic segment of the facial canal, the incudo-stapedial joint, the proximal vestibular aqueduct, the interscalar septum, and the modiolus) had higher contrast and less partial-volume effect with VCT. CONCLUSION: The flat-panel prototype provides better definition of fine osseous structures of temporal bone than that of currently available MSCT scanners. This study provides impetus for further research in increasing spatial resolution beyond that offered by the current state-of-the-art scanners.